Arqueologia da paisagem de um patrimônio da humanidade: o caso da Cidade Velha Cabo Verde - Angela de Jesus Gonçalves Varela (2016)
This study aims to understand the logics of implantation and organization of material culture on the landscape through an archaeological perspective. The ancient city Ribeira Grande, currently known as Cidade Velha, was selected as the case study. This site was chosen due to its historical role during the triangular trade. Due to its geo-strategic position, Cidade Velha was a mandatory passage port for all Atlantic marine flux, becoming an attractive site for the navigators. Its occupation and space colonization demanded the introduction of peoples, plants, and animals, because it was, until then, unoccupied. Considering this logics, the landscape was consciously built by the Portuguese colonizer, aiming to affirm power over the territory and its subjects. In this sense, this study focused on the analysis of the structures that testify the exercise and legitimation of power. Considering the new approaches in archaeology, the material culture was analyzed as a result of human action charged with intentionality and meanings. Thus, the study of the historical site, under an archaeological perspective, makes possible to present new interpretations about the social and cultural world of those actors who participated in the construction of the city: Portuguese, Africans, And mestizos. In this sense, the structures reveal the ideology, the power discourses, and the social relations and practices.